Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Gulf of Mexico)--American oyster - Stanley, Jon G. (U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.64)